2019
DOI: 10.21037/apm.2019.10.05
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of levofloxacin on macrolide-unresponsive and corticosteroid-resistant refractory Mycoplasma pneumoniae pneumonia in children

Abstract: Background: This study aimed to summarize the experience in treatment of Mycoplasma pneumoniae pneumonia (MPP) with worsening lung shadow despite treatment with appropriate antimicrobials and corticosteroid in children.Methods: All patients satisfied refractory MP pneumonia (RMPP) diagnostic criteria were enrolled. The clinical manifestations, laboratory findings, imaging features, treatments, and outcomes were retrospectively reviewed.Results: Six patients with an average age of 7.83±3.13 years old were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…A previous study showed that a reduced MP-DNA copy number in the sputum was well correlated with patients' clinical symptoms and the therapeutic efficacy of antibiotics [34]. Studies have shown that levofloxacin and minocycline therapy in patients who are nonresponsive to macrolides may reduce their fever duration and result in a more rapid decrease in the sputum MP-DNA copy number [35,36]. Despite the efficacy of fluoroquinolones, clinicians should be aware of the adverse reactions (musculoskeletal adverse events), and the usage of fluoroquinolones should be based on in vitro activity and disease severity in children with MPP.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that a reduced MP-DNA copy number in the sputum was well correlated with patients' clinical symptoms and the therapeutic efficacy of antibiotics [34]. Studies have shown that levofloxacin and minocycline therapy in patients who are nonresponsive to macrolides may reduce their fever duration and result in a more rapid decrease in the sputum MP-DNA copy number [35,36]. Despite the efficacy of fluoroquinolones, clinicians should be aware of the adverse reactions (musculoskeletal adverse events), and the usage of fluoroquinolones should be based on in vitro activity and disease severity in children with MPP.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that a reduced MP-DNA copy number in the sputum was well correlated with patients' clinical symptoms and the therapeutic e cacy of antibiotics [33] . Studies have shown that levo oxacin and minocycline therapy in patients who are nonresponsive to macrolides may reduce their fever duration and result in a more rapid decrease in the sputum MP-DNA copy number [34,35] . Despite the e cacy of uoroquinolones, clinicians should be aware of the adverse reactions (musculoskeletal adverse events), and the usage of uoroquinolones should be based on in vitro activity and disease severity in children with MPP.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that a reduced MP-DNA copy number in the sputum was well correlated with patients' clinical symptoms and the therapeutic e cacy of antibiotics [34] . Studies have shown that levo oxacin and minocycline therapy in patients who are nonresponsive to macrolides may reduce their fever duration and result in a more rapid decrease in the sputum MP-DNA copy number [35,36] . Despite the e cacy of uoroquinolones, clinicians should be aware of the adverse reactions (musculoskeletal adverse events), and the usage of uoroquinolones should be based on in vitro activity and disease severity in children with MPP.…”
Section: Discussionmentioning
confidence: 99%